UN Convention on the rights of the child thirty years later: achievements and challenges (case of Latin America) - T. A. Medvedeva (Ибероамериканские тетради, 2019)
The paper examines the socio-economic situation of children and adolescents inLatin Americaand the dynamics of its change in the light of the adoption of the UN Convention on the rights of the child in 1989. The main directions of state policy for the protection of children’s rights are analyzed taking into account the specific features of the regional situation and in the context of the principles underlying the concept of sustainable development. The main attention is paid to the analysis of the formation of new state mechanisms, the so called comprehensive system of protection of children and adolescents, as well as methods of ensuring their social rights and programs aimed at combating child poverty-an acute problem in the field of rights.